2019
DOI: 10.1097/bot.0000000000001375
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Prescribing Practices After Common Isolated Lower Extremity Injuries

Abstract: Objective: This retrospective study aimed at identifying opiate prescribing practices, the number of morphine milligram equivalents (MMEs) prescribed by orthopaedic and nonorthopaedic providers in patients with operatively treated isolated lower extremity fractures, and provide opiate prescribing recommendations. Methods: Patients older than 18 years with isolated lower extremity (unicondylar, bicondylar, tibial shaft, pilon, and ankle) fractures betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Five studies [ 7 , 9 , 21 23 ] reported the incidence of adverse effects. Pooled results showed that ibuprofen group had 41% lower risk of adverse events than control group (RR = 0.59; 95% CI, 0.45 to 0.79; I 2 = 21%; P = .0002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies [ 7 , 9 , 21 23 ] reported the incidence of adverse effects. Pooled results showed that ibuprofen group had 41% lower risk of adverse events than control group (RR = 0.59; 95% CI, 0.45 to 0.79; I 2 = 21%; P = .0002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, opioids are commonly prescribed for pain relief after acute injuries [23] . Unfortunately, opioids may lead to significant adverse events (e.g., somnolence, delirium, respiratory depression, abuse, dependence and addiction), creating a need for better alternatives [21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of delayed compared to those of early treatment of a tibial pilon fracture are deemed to include a clean and stable fracture environment for reduction, control of soft tissue swelling and local hematoma, and ensuring adequate microcirculation of the middle and lower segments of the tibia to support fracture healing and recovery of local soft tissues, including function of the tibial nerve[ 10 ]. Previous studies have reported a shorter time to fracture healing and full weight-bearing, as well as a reduced risk of fracture non-union, with delayed compared to early fracture reduction and internal fixation[ 11 , 12 ]. Our findings indicate that factors other than the time of surgery, namely the fracture type, the presence/absence of wound contamination, type of incision used, and health comorbidities influence the risk postoperative infection.…”
Section: Discussionmentioning
confidence: 99%
“…13 Plateau fractures also frequently have associated soft tissue compromise, including injuries to the menisci, collateral, and cruciate ligaments. 14,15 Patient-specific risk factors for increased and/or prolonged postoperative opioid use include patients with bicondylar tibial plateau fractures, 16 external fixation, and intra-articular fracture. 17 There is currently a dearth of literature evaluating the impact of RA on longitudinal perioperative and postoperative opioid demand in tibial plateau fractures.…”
mentioning
confidence: 99%